DAMPAK MODERNISASI PERTANIAN DAN INFRASTRUKTUR JALAN TANI TERHADAP PERUBAHAN SOSIAL DI DESA PAROTO - Firman; Muh. Tahir Kasnawi; Muh. Iqba Latief (Halu Oleo University, 2025)
This research aims to analyse the impact of implementing agricultural activities on social change in Paroto Village. Agricultural activities are the main sector that sustains people's lives in this village, and their implementation affects not only economic but also social aspects. This research used a descriptive qualitative approach with data collection methods through in-depth interviews, observation, and documentation studies. The results showed that changes in agricultural activities, especially with the presence of modernisation and improved access to farm road infrastructure, have affected work patterns, social relations, and the community's economic structure. Agricultural modernisation, such as the use of mechanical tools and crop diversification, has encouraged changes in family roles as well as increased participation of women and youth in the agricultural sector. In addition, openness to new technologies has also strengthened social interactions between farmers, the government, and local institutions. In conclusion, implementing agricultural activities in Paroto Village has played a significant role in driving more dynamic and inclusive social change.